Examples with solutions for Extracting Square Roots: Using short multiplication formulas

Exercise #1

Solve the following equation:

(x1)2=x2 (x-1)^2=x^2

Video Solution

Step-by-Step Solution

Let's examine the given equation:

(x1)2=x2 (x-1)^2=x^2 First, let's simplify the equation, using the perfect square binomial formula:

(a±b)2=a2±2ab+b2 (a\pm b)^2=a^2\pm2ab+b^2 ,

We'll start by opening the parentheses on the left side using the perfect square formula and then move terms and combine like terms, in the final step we'll solve the resulting simplified equation:

(x1)2=x2x22x1+12=x2x22x+1=x22x=1/:(2)x=12 (x-1)^2=x^2 \\ \downarrow\\ x^2-2\cdot x\cdot1+1^2=x^2\\ x^2-2x+1= x^2\\ -2x=-1\hspace{6pt}\text{/}:(-2)\\ \boxed{x=\frac{1}{2}} Therefore, the correct answer is answer A.

Answer

x=12 x=\frac{1}{2}

Exercise #2

Solve the following equation:

(x+1)2=x2 (x+1)^2=x^2

Video Solution

Step-by-Step Solution

Let's examine the given equation:

(x+1)2=x2 (x+1)^2=x^2 First, let's simplify the equation, using the perfect square binomial formula:

(a±b)2=a2±2ab+b2 (a\pm b)^2=a^2\pm2ab+b^2 ,

We'll start by opening the parentheses on the left side using the perfect square formula and then move terms and combine like terms, in the final step we'll solve the simplified equation we obtain:

(x+1)2=x2x2+2x1+12=x2x2+2x+1=x22x=1/:2x=12 (x+1)^2=x^2 \\ \downarrow\\ x^2+2\cdot x\cdot1+1^2=x^2\\ x^2+2x+1= x^2\\ 2x=-1\hspace{6pt}\text{/}:2\\ \boxed{x=-\frac{1}{2}} Therefore, the correct answer is answer A.

Answer

x=12 x=-\frac{1}{2}

Exercise #3

Solve the following equation:

(x+2)212=x2 (x+2)^2-12=x^2

Video Solution

Step-by-Step Solution

Let's examine the given equation:

(x+2)212=x2 (x+2)^2-12=x^2 First, let's simplify the equation, for this we'll make use of the perfect square binomial formula:

(a±b)2=a2±2ab+b2 (a\pm b)^2=a^2\pm2ab+b^2 ,

We'll start by opening the parentheses on the left side using the perfect square formula and then move terms and combine like terms, in the final step we'll solve the simplified equation we obtain:

(x+2)212=x2x2+2x2+2212=x2x2+4x+412=x24x=8/:4x=2 (x+2)^2-12=x^2 \\ \downarrow\\ x^2+2\cdot x\cdot2+2^2-12=x^2\\ x^2+4x+4-12= x^2\\ 4x=8\hspace{6pt}\text{/}:4\\ \boxed{x=2} Therefore, the correct answer is answer C.

Answer

x=2 x=2

Exercise #4

Solve the following equation:

(x+3)2=(x3)2 (x+3)^2=(x-3)^2

Video Solution

Step-by-Step Solution

Let's examine the given equation:

(x+3)2=(x3)2 (x+3)^2=(x-3)^2 First, let's simplify the equation, for this we'll use the perfect square formula for a binomial squared:

(a±b)2=a2±2ab+b2 (a\pm b)^2=a^2\pm2ab+b^2 ,

We'll start by opening the parentheses on both sides simultaneously using the perfect square formula mentioned, then we'll move terms and combine like terms, and in the final step we'll solve the resulting simplified equation:

(x+3)2=(x3)2x2+2x3+32=x22x3+32x2+6x+9=x26x+9x2+6x+9x2+6x9=012x=0/:12x=0 (x+3)^2=(x-3)^2 \\ \downarrow\\ x^2+2\cdot x\cdot3+3^2= x^2-2\cdot x\cdot3+3^2 \\ x^2+6x+9= x^2-6x+9 \\ x^2+6x+9- x^2+6x-9 =0\\ 12x=0\hspace{6pt}\text{/}:12\\ \boxed{x=0} Therefore, the correct answer is answer A.

Answer

x=0 x=0

Exercise #5

Solve the following equation:

(x+1)2=(2x+1)2 (-x+1)^2=(2x+1)^2

Video Solution

Answer

x1=0,x2=2 x_1=0,x_2=-2